FLUKTUASI SUHU UDARA PADA EKOSISTEM HUTAN KOTA - Nonong Krisnawati Loha; Johan A. Rombang; Josephus I. Kalangi (COCOS, 2022)
Abstract This study aims to determine fluctuations in air temperature in urban forest ecosystems. This research was carried out in 3 (three) places, namely Tomohon urban forest (921 meter above sea level), Bitung urban forest (Danowudu 248 meter above sea level) North Minahasa urban forest (Kenangan 342 meter above sea level), conducted in November 2021, for 5 days. Observation plots measuring 25x25 m at each location. The diameter of the crown was measured using the "Improvised technique". The results showed that, Danowudu urban forest had a tree density level of 0.0192 trees/m² with a diversity of 6 tree species, Tomohon urban forest had a tree density of 0.0224 trees/m² with a diversity of 3 tree species, and Kenangan urban forest had a tree density of 0.0272 trees/m² with a diversity of 5 tree species, the highest temperature fluctuation was obtained in the Kenangan urban forest at 7.48°C and the lowest at 5.08°C in the Tomohon urban forest. Keywords: Air temperature, fluctuation, urban forest